2018
DOI: 10.1038/s41386-018-0117-6
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species evidence from human and rat brain transcriptome for growth factor signaling pathway dysregulation in major depression

Abstract: An enhanced understanding of the pathophysiology of depression would facilitate the discovery of new efficacious medications. To this end, we examined hippocampal transcriptional changes in rat models of disease and in humans to identify common disease signatures by using a new algorithm for signature-based clustering of expression profiles. The tool identified a transcriptomic signature comprising 70 probesets able to discriminate depression models from controls in both Flinders Sensitive Line and Learned Hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…Regarding the association of the serum levels of leptin with stroke, the opinion of scholars is divided. By contrast, a prospective study on 4,571 healthy African Americans did not identify any association between leptin levels and ischemic stroke risk in either men or women (8,22,51,86). Only a few small studies evaluated leptin levels during the acute phase of ischemic stroke and reported increased leptin levels (7,26,50,52,87).…”
Section: Discussionmentioning
confidence: 76%
“…Regarding the association of the serum levels of leptin with stroke, the opinion of scholars is divided. By contrast, a prospective study on 4,571 healthy African Americans did not identify any association between leptin levels and ischemic stroke risk in either men or women (8,22,51,86). Only a few small studies evaluated leptin levels during the acute phase of ischemic stroke and reported increased leptin levels (7,26,50,52,87).…”
Section: Discussionmentioning
confidence: 76%
“…On the contrary, no SNPs of FGFR2 gene was associated with depression (Wang et al, 2012). At the transcriptional level, the enrichment of FGF pathways is found both in depressed patients and rat models by gene expression analysis (Carboni et al, 2018).…”
Section: Fgfs and Depressionmentioning
confidence: 99%
“…[14] So far, there are many studies which investigated MDD-related mRNAs in blood tissue and brain tissue, and they are considered to better utilize the rich and comprehensive information in omics data to explore the underlying molecular biology of MDD. [1517]…”
Section: Introductionmentioning
confidence: 99%